Strategic Alliances in Knowledge-Intensive Industries: An Integrated View - Yongliang Stanley Han; Xiang Liu (Journal of Accounting, Business and Management (JABM), 2018)
In this study, we examine strategic alliances between large pharmaceutical companies (LPCs) and new biotechnology firms (NBFs) in the knowledge-intensive biopharmaceutical industry in the light of two explanations for the motives behind R&D alliances, namely, the transaction cost explanation and the learning with flexibility explanation. We develop a series of propositions based on an integrated view of the motives behind strategic alliances in knowledge-based industries.